2001
DOI: 10.5194/aab-44-441-2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on sarcoplasmic reticulum Ca<sup>2+</sup> transport in muscle of mouse lines long-term selected for different Performance traits

Abstract: SummaryMouse lines used were long-term selected for high (DU-hTP) or low treadmill Performance (DU-ITP), or high locomotor open field activity (DU-hOF). The control line DU-Ks was maintained unselected. For each line 30 mice were used at 42 days of age. All lines were split into three groups: the first group was investigated without running exercise, the second had to run 500 m, and the third had to run until exhaustion on the treadmill. Compared to mice without running, in exhausted mice the maximal rate of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In particular, exercise attenuates Ca 2+ uptake and SR Ca 2+ -ATPase activity (Byrd et al 1989a(Byrd et al , 1989bLuckin et al 1991;Gollnick et al 1991;Booth et al 1997) or SR Ca 2+ release (Favero et al 1993;Westerblad et al 1998, Ortenblad et al 2000. Kuchenmeister et al (2001) reported that pre-slaughter stress in pigs also influenced Ca 2+ uptake. In sheep, pre-slaughter exercise elicited an 18% reduction in Ca 2+ uptake, but this was not found to be significantly different to the uptake rates in the non-exercised controls.…”
Section: Pre-slaughter Stressmentioning
confidence: 99%
“…In particular, exercise attenuates Ca 2+ uptake and SR Ca 2+ -ATPase activity (Byrd et al 1989a(Byrd et al , 1989bLuckin et al 1991;Gollnick et al 1991;Booth et al 1997) or SR Ca 2+ release (Favero et al 1993;Westerblad et al 1998, Ortenblad et al 2000. Kuchenmeister et al (2001) reported that pre-slaughter stress in pigs also influenced Ca 2+ uptake. In sheep, pre-slaughter exercise elicited an 18% reduction in Ca 2+ uptake, but this was not found to be significantly different to the uptake rates in the non-exercised controls.…”
Section: Pre-slaughter Stressmentioning
confidence: 99%
“…In some physiological and mainly pathological states muscle growth is determined solely at the catabolic side (eg. muscular atrophy after denervation and tenotomy, chemically and hormonally induced changes) (KÜCHENMEISTER et al, 2001;KÜCHEN-MEISTER and KUHN, 2003) The process of protein catabolism involves a nonlysosomal and lysosomal route of intracellular protein catabolism. The calciumdependent neutral proteolytic system consisting of µ-and m-calpain and their natural inhibitor calpastatin, do not degrade any of the major myofibrillar proteins like myosin and actin (THOMPSON and PALMER, 1998;GOLL et al, 1998;JOHARI et al, 1993).…”
Section: Introductionmentioning
confidence: 99%